Emotional Freedom Techniques: A Pathway to Stress Relief and Body Detox - Ullagaddi, Rajeshwari (Journal of Neonatal Surgery, 2025)
Emotional Freedom Techniques (EFT) is an integrative mind-body approach fusing cognitive elements with acupressure tapping to address emotional distress and physiological disturbance. Growing evidence suggests that EFT affects major biochemical pathways involved in inflammation and oxidative stress, which are fundamental to chronic illnesses and impaired detoxification processes, in addition to improving psychological well-being. This review examines the ways EFT affects the body's biochemical environment to promote detoxification and healing. Chronic psychological stress turns on the hypothalamic-pituitary-adrenal (HPA) axis, which results in high cortisol levels and pro-inflammatory cytokines. Ongoing inflammation and oxidative stress cause cellular damage and compromised activity of endogenous antioxidant systems including superoxide dismutase (SOD) and glutathione. EFT could downregulate inflammatory responses and oxidative load by controlling autonomic nervous system activity and lowering stress indicators. Following EFT treatments, emerging clinical studies show drops in cortisol, C-reactive protein (CRP), and subjective stress indicators, therefore pointing to a boost in systemic detoxification ability that might improve hepatic biotransformation and the immune system. Using EFT, the mind-body connection provides a whole approach for encouraging biochemical resilience and supporting the body's natural detoxification channels. Ultimately, EFT may be an easy-to-use, non-invasive addition to traditional detoxification techniques, helping to achieve sustainable health and well-being. Larger, biomarker-driven studies are essential to unravel the underlying molecular mechanisms and enhance the effectiveness of EFT for both environmental and clinical health applications.